Improving access to tuberculosis preventive treatment for children in Ethiopia: designing a home-based contact management intervention for the CHIP-TB trial through formative research - Nicole Salazar-Austin; Alanna J. Bergman; Christiaan Mulder; Carrie Tudor; Fiseha Mulatu; Gidea Conradie; Richard E. Chaisson; Jonathan E. Golub; Gavin Churchyard; Ahmed Bedru; Deanna Kerrigan (BMC, 2024)
Abstract Background Tuberculosis (TB) preventive treatment (TPT) is a long-standing recommendation for children exposed to TB but remains poorly implemented. Home-based contact management may increase access and coverage of TPT among children exposed to TB in their households. Methods Sixty in-depth interviews were conducted with key informants including program managers, TB providers (known as TB focal persons), health extension workers and caregivers whose children had recently engaged with TB prevention services in Oromia, Ethiopia in 2021 to understand the barriers and facilitators to providing home-based TB prevention services for children aged < 15 years. Thematic content analysis was conducted including systematically coding each interview. Results Home-based services were considered a family-centered intervention, addressing the time and financial constraints of clients. Stakeholders proposed a task-shared intervention between health extension workers and facility-based TB focal persons. They recommended that TB services be integrated into other home-based services, including HIV, nutrition, and vaccination services to reduce workload on the already overstretched health extension workers. Community awareness was considered essential to improve acceptability of home-based services and TPT in general among community members. Conclusions Decentralization of TPT should be supported by task-sharing initiation and follow up between health extension workers and facility-based TB focal persons and integration of home-based services. Active community engagement through several existing mechanisms can help improve acceptability for both home-based interventions and TPT promotion overall for children. Trial registration The results presented here were from formative research related to the CHIP-TB Trial (Identifier NCT04369326) registered on April 30, 2020. This qualitative study was separately registered at NCT04494516 on 27 July 2020.